The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio as a predictor of all cause and cardiovascular mortality in United States adults with NAFLD: a prospective cohort study - Lisha Yang; Jingwen Li; Yilian Xie; Guoqing Qian (BMC Gastroenterology)
Abstract Background The non-HDL cholesterol to HDL cholesterol ratio (NHHR) is a novel composite lipid index. However, its relationship with mortality, particularly in individuals with non-alcoholic fatty liver disease (NAFLD), remains unclear. The aim of this study was to explore the association between NHHR and both all-cause and cardiovascular mortality in adults with NAFLD in the United States. Methods This study included 12,648 adult participants with NAFLD from the National Health and Nutrition Examination Survey (NHANES) database (1999–2018). Multivariate Cox proportional hazards models and restricted cubic spline (RCS) methods were employed to assess all-cause and cardiovascular mortality. Subgroup analyses were performed to verify the consistency of these associations. Results Over a median follow-up of 99.27 months, 1,659 participants died from all causes, including 460 from cardiovascular disease. RCS analysis revealed a U-shaped relationship between NHHR and all-cause mortality, no association was found between NHHR and cardiovascular mortality. The inflection points for all-cause mortality were 2.67. Subgroup analysis showed that a stronger association between NHHR and all-cause mortality in those with diabetes(P = 0.048). Conclusions NHHR is associated with all-cause mortality in NAFLD patients, with distinct non-linear relationships, while it is not associated with cardiovascular mortality. NHHR monitoring may be valuable for assessing mortality risk, particularly in those with diabetes.